Kant's critique of pure reason : an introduction - Buroker, Jill Vance (New York : Cambridge university press, 2006)
This introductory textbook explains the role of the first Critique in Kant's philosophy and offers a line-by-line reading of the major arguments in the text.
1. Introduction to the critical project; 2. The prefaces and the introduction; 3. The transcendental aesthetic; 4. The metaphysical deduction; 5. The transcendental deduction; 6. The schematism and the analytic of principles I; 7. The analytic of principles II; 8. Transcendental illusion I: rational psychology; 9. Transcendental illusion II: rational cosmology; 10. Transcendental illusion III: rational theology; 11. Reason and the critical philosophy; Conclusion: Kant's transcendental idealism
Includes bibliographical references and index.
Keywords: Causality; Kant, Immanuel 1724-1804.; Causation